Injuries to the head and face in 0-4-year-old child victims of fatal external causes in Campina Grande, PB, Brazil - Cavalcanti, Alessandro Leite; Barros De Alencar, Catarina Ribeiro (The Turkish Journal of Pediatrics, 2010)
We evaluated the presence of injuries to the head and face in Brazilian 0-4-year-old child victims of fatal external causes by analyzing forensic medical reports derived from all autopsies performed in 0-4-year-old children at the Department of Forensic Medicine of the city of Campina Grande, PB, Brazil, between January 2003 and December 2007. The study sample consisted of 81 reports (1.8%) referring to children who were confirmed to have died from external causes. Most victims were males (56.8%) and 1 year of age (27.2%). Drowning (34.6%) and motor vehicle accidents (22.2%) were the most common causes of death. Injuries to the head and to the face were found in 33.3% and 34.6% of the victims, respectively. There was a strong association between the occurrence of motor vehicle accidents and the presence of injuries to the head (p < 0.01; odds ratio [OR]=21.25 [5.29-85.31]) and to the face (p < 0.01; OR = 19.23 [4.83-76.56]). There was also an association between the existence of injuries to the head and presence of maxillofacial injuries (p < 0.01; OR = 5.09 [1.87-13.84]). Drowning and motor vehicle accidents were the main causes of death in children aged 0 to 4 years. Parents should adopt measures to make the home environment safer and prevent fatal accidents by limiting their children’s access to pools and cisterns. Reduction in child mortality from motor vehicle accidents involves parental vigilance in the road traffic environment and home education on driveway safety.